The Influence of Learning Management System Paltform on Learners’ Performance in Suzhou Early Chilhood Education College of China - Sun, Jingyi; Phakamach, Phongsak (Jurnal Edusci, 2024)
The purpose of this study is to explore the impact of learning management system (LMS) platform on learners' performance in Suzhou Early Childhood Education College. The interactive activities of the learning management system platform are taken as independent variables and learner performance as dependent variables. This study adopts quantitative research method and collects data through questionnaire survey to evaluate the specific impact of different interactive activities on learners' achievement. The results show that the interaction between learners and the system has a significant impact on the performance of learners, and the interaction between learners and teachers has a significant impact on the performance of learners, while the interaction between learners has no significant impact on the performance of learners. In addition, the study also found that learners of different ages and grades, as well as the nature of learning courses, have different interactive needs and preferences for learning management system platforms, which suggests that educators should consider individual differences when designing and implementing learning management systems. The conclusion of this study has important practical significance for optimizing the design of learning management system platform and improving the learning effect of learners. At the same time, it also provides data support and theoretical reference for future research in related fields.